2002
DOI: 10.1074/jbc.m105324200
|View full text |Cite
|
Sign up to set email alerts
|

Mutation of Residue 33 of Human Equilibrative Nucleoside Transporters 1 and 2 Alters Sensitivity to Inhibition of Transport by Dilazep and Dipyridamole

Abstract: Human equilibrative nucleoside transporters (hENT) 1 and 2 differ in that hENT1 is inhibited by nanomolar concentrations of dipyridamole and dilazep, whereas hENT2 is 2 and 3 orders of magnitude less sensitive, respectively. When a yeast expression plasmid containing the hENT1 cDNA was randomly mutated and screened by phenotypic complementation in Saccharomyces cerevisiae to identify mutants with reduced sensitivity to dilazep, clones with a point mutation that converted Met 33 to Ile (hENT1-M33I) were obtaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
134
2
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 128 publications
(147 citation statements)
references
References 41 publications
10
134
2
1
Order By: Relevance
“…Conserved Gly residues within transmembrane domains (TM) 4 and 5 of human ENT1 (hENT1) and TM5 of LdNT1 have been shown to be critical for transport function and ligand selectivity (4,5), and a Leu within TM2 of hENT1 has also been revealed as a ligand specificity determinant (6). Additional studies have supported a role for TMs 3-6 (7) and Met 33 within TM1 of hENT1 in the binding of dipyridamole and dilazep (8). Dipyridamole and dilazep are potent inhibitors of hENT1 but do not significantly affect the majority of parasite nucleoside transporters (9).…”
mentioning
confidence: 88%
“…Conserved Gly residues within transmembrane domains (TM) 4 and 5 of human ENT1 (hENT1) and TM5 of LdNT1 have been shown to be critical for transport function and ligand selectivity (4,5), and a Leu within TM2 of hENT1 has also been revealed as a ligand specificity determinant (6). Additional studies have supported a role for TMs 3-6 (7) and Met 33 within TM1 of hENT1 in the binding of dipyridamole and dilazep (8). Dipyridamole and dilazep are potent inhibitors of hENT1 but do not significantly affect the majority of parasite nucleoside transporters (9).…”
mentioning
confidence: 88%
“…The presence of nucleoside transporters was described in several tissues and central nervous system areas (Cass et al 1998, Parkinson 1999) and subdivided in two major subclasses, concentrative (CNTs, sodium-dependent) and equilibrative (ENTs, sodium-independent) (Visser et al 2002). The equilibrative transporters are ubiquitously distributed and further classified as sensitive (es or ENT1) or insensitive (ei or ENT2) to the inhibitor Nitrobenzylthioinosine (NBI).…”
Section: -Adenosine Transport Sitesmentioning
confidence: 99%
“…The most notable characteristic of ENT1-mediated transport is that it can be inhibited by extremely low concentrations of NBMPR and dipyridamole; for example, their respective K i values for human ENT1 (hENT1) are 6 and 48 nM, respectively. 29) (Detailed information on the physiology and function of ENTs as nucleoside transporters can be found elsewhere. 30,31) ) Recently, Yao et al have demonstrated that, in the Xenopus laevis oocyte expression system, ENT1 has the capability to transport not only nucleosides but also nucleobases such as adenine, hypoxanthine, guanine, thymine, and uracil 8) (Table 1).…”
Section: Facilitative Transport Systemsmentioning
confidence: 99%